HUMAN RESOURCE PERFORMANCE IN MAINTAINING PREMIUM ELECTRONIC PRODUCT QUALITY: A REVIEW OF KAIZEN PHILOSOPHY AND COUNTRY OF ORIGIN EFFECT - Darmawan, Didit; Aprilia, Eliya Putri (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This literature review examines the internalization of Kaizen philosophy within human resources and its correlation with performance consistency in the premium electronics industry, while also analyzing how the country of origin effect shapes workers' professional identity. The study employs a qualitative literature review method, synthesizing theoretical perspectives from management, organizational behavior, and cross-cultural psychology. The analysis reveals that Kaizen internalization transforms individual consciousness through personal discipline, employee empowerment, systematic thinking habits, and intrinsic motivation reinforcement, enabling workers to maintain quality standards autonomously. Simultaneously, the Made in Japan label creates a complex psychological landscape where workers navigate between imported standards and local values through continuous identity negotiation. Successful internalization occurs when workers achieve authentic appropriation of these values, making quality preservation an expression of professional self-identity rather than mere procedural compliance. The theoretical contribution lies in bridging the gap between quality philosophy and individual performance through psychological mechanisms, while extending country of origin discourse to internal organizational dynamics. Practically, this review suggests that companies should design cultural development programs addressing affective dimensions and create cross-cultural dialogues enabling workers to integrate global standards with local wisdom harmoniously, ensuring sustainable quality consistency in premium electronic products.